Fa’āliyyatu Istikhdāmu Kitab Al Hilāl Fῑ Fanni Al Lughah Al Arobiyyah Fῑ Tarqiyyati Mahāroti Al Kalāmi - Arisandi, Yusuf; Rafli Ramble (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
The use of the book Hilal Fii Fann Lughah Al'Arabiyyah in learning Arabic at the Ar Riyadh Islamic boarding school because researchers found that students at the boarding school were heterogeneous, while the books used by teachers used many foreign words which were rarely used in everyday conversations. The objectives of this study are: 1) To find out how to use the book Hilal Fii Fann Lughah Al'Arabiyyah in improving speaking skills at the Ar Riyadh Islamic boarding school. 2) Knowing how effective the use of the book Hilal Fii Fann Lughah Al'Arabiyyah is in improving speaking skills at the Ar Riyadh Islamic boarding school. The approach used by researchers is a quantitative experimental approach. Because the researcher needs the big picture or to provide a numerical description that shows the approximation of this phenomenon, its size and degree of association with other phenomena. The data sources are teachers and students, data collection methods using observation, interviews, documentation and questionnaires. The results of this study can be concluded by the researchers as follows: 1) The use of the book Hilal Fii Fann Lughah Al'Arabiyyah at the Ar Riyadh Islamic Boarding School is fairly good, this can be seen from 86% of students choosing to study using the book. 2) The use of the book Hilal Fii Fann Lughah Al'Arabiyyah for students of class 1 “C” Ar Riyadh Islamic Boarding School has been effective, as evidenced by the results in the pre- and post-test of each group it has become clear to researchers that there is a statistically significant difference from each side, where the degree of T reached 5.38 for the experimental group.